Estudo da temperatura final, pressão final e do ponto de injeção a partir de simulação computacional e metodologia de superfície de resposta - Silva, Joeline Dutra (Brasil, 2024)
Plastic injection molding is a technique widely used in several areas of industry, from aerospace to packaging, making up an important part of financial transactions in Brazil. Variables such as injection time, cooling time, mold temperature, machine temperature, injection speed, injection pressure, injection point positioning are important for the process result. Thus, this work proposed to study, through statistical analysis, the influence of the injection point positioning on the result of the variables final temperature and final pressure of plastic injection made by computational simulation. For this, Solidworks Plastics® software was used for plastic injection simulation and Minitab for statistical analysis. The results showed that the factorial design and the CCD methodology achieve results in a regression analysis that are as satisfactory as a planning with all possible combinations for the predictor variables. The injection point has a greater influence on the final pressure response variable, and may also influence the final temperature optimization results depending on the desired result. At the end of the process, the pressure is higher near the injection point and lower the further away from it, so the location of the PI has an influence on problems related to settlement and stress accumulation when related to the final pressure response variable.